2004
DOI: 10.1016/j.amjcard.2004.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve of the angiographically normal left anterior descending coronary artery in patients with remote coronary artery disease

Abstract: Coronary artery disease (CAD) has been suggested to alter coronary flow reserve (CFR; the ratio between hyperemic and baseline coronary flow velocities) not only in territories supplied by stenotic arteries but also in angiographically normal, remote regions. However, few data exist regarding the left anterior descending (LAD) coronary artery as the normal index artery. The influence of remote CAD on CFR of the angiographically normal LAD was evaluated with transthoracic Doppler ultrasound to measure CFR in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…It seems attractive and easy to detect coronary stenoses basing on the search of the aliasing zone and the measurement of peak diastolic flow velocity only, but both methods are semiquantitative and, unfortunately, inaccurate. As previously reported, laminar peak diastolic velocity in the coronary artery is from 0.21 ± 0.08 m/s (Youn et al, 2002 to 0.28 ± 0.09 m/s (Pizzuto F., 2004), and the velocity will not exceed 1 m/s even in case of its 3-4-fold increase in the stenosis site. So, local peak diastolic flow velocity >2.0 m/s is a highly specific, but low sensitive marker of coronary artery stenosis.…”
Section: Focal Aliasing and Flow Acceleration In The Site Of A Signifsupporting
confidence: 49%
See 3 more Smart Citations
“…It seems attractive and easy to detect coronary stenoses basing on the search of the aliasing zone and the measurement of peak diastolic flow velocity only, but both methods are semiquantitative and, unfortunately, inaccurate. As previously reported, laminar peak diastolic velocity in the coronary artery is from 0.21 ± 0.08 m/s (Youn et al, 2002 to 0.28 ± 0.09 m/s (Pizzuto F., 2004), and the velocity will not exceed 1 m/s even in case of its 3-4-fold increase in the stenosis site. So, local peak diastolic flow velocity >2.0 m/s is a highly specific, but low sensitive marker of coronary artery stenosis.…”
Section: Focal Aliasing and Flow Acceleration In The Site Of A Signifsupporting
confidence: 49%
“…Pizzuto et al, 2001 revealed CFVR value for the LAD ranging from 2.90±0.58 to 3.050.81 in control group of patients with angiographically normal coronary arteries, and similar values for CFVR were found in <50% LAD in-stent restenosis (Lambertz et al, 1999;. Later, CFVR in angiographically normal LAD patients with remote CAD (presence of previous remote myocardial infarction and wall motion abnormalities) was determined also as preserved (Pizzuto et al, 2004). According to numerous studies using TTE the cut-off value of CFVR is generally accepted to be 2.0 for predicting significant LAD stenosis in patients under decision-making process, after intracoronary intervention, and with in-stent restenosis (table 6).…”
Section: Cut-off Level For Normal and Pathologic Cfvr 421 Tte Calcumentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 As discussed above, this could potentially have implications for the assessment of FFR in nonculprit vessels in patients presenting with ACS.…”
Section: Nonculprit Arteriesmentioning
confidence: 99%